Pengaruh Plant Therapy terhadap Kemampuan Bersosialisasi Pasien Skizofrenia - Herlina, Nadia; Sumirta, I Nengah; Candra, I Wayan; Runiari, Nengah (Jurnal Gema Keperawatan, 2024)
Individuals with schizophrenia often experience problems in social interaction due to a decrease in social skills which is part of the symptoms of schizophrenia. The purpose of this study is to determine the effect of plant therapy on the decline of social skills in schizophrenia patients. This research method uses pre-experimental one-group pretest-posttest research design. The sample collection by using the techniques of total sampling. Number of samples as many as 25 people. Data collection using questionnaires ability to socialize This study used the Wilcoxon Signed Rank Test with a significant ρ-value of 0,000. The results of this study show that before carrying out Plant Therapy intervention in the aspect of daily living activity, most of the categories are lacking. In terms of social behavior, most categories are lacking. In terms of occupational behavior, most of the categories are sufficient and lacking. After being given the intervention, Plant Therapy has improved in the aspect of daily living activity, most of the good categories. In terms of social behavior, most of the categories are good. In terms of occupational behavior, most of the categories are very good and good. The conclusion of this study is that there is an effect of Plant Therapy on the decrease in social skills in schizophrenia patients, p-value = 0,000.